A synthesis of (arylthio-ethylidene)indolin-2-ones via S-arylation of oxoindolin-ethanethiolates with aryl halides. (4th March 2019) - Yavari, Issa; Taheri, Zohreh; Sheikhi, Sara; Halvagar, Mohammad Reza
ABSTRACT: Aryl-sulfur bond formation between aryl halides and 1-(2-oxoindolin-3-ylidene)-2-aroylethanethiolates, prepared from isatin, 1-aryl-2-thiocyanatoethan-1-ones, and aryl halides, catalyzed by copper(I) iodide in DMF at 80°C afforded a nearly 1:1 mixture of ( Z/E )-3-(2-oxo-2-aryl-1-(arylthio)ethylidene)indolin-2-ones, in good yields. The stereochemistry of these products has been confirmed by X-ray diffraction studies. GRAPHICAL ABSTRACT: